PENGARUH CAMPURAN BIOETANOL DAN KONDUKTIVITAS TERMAL ELEKTRODA BUSI TERHADAP EMISI GAS BUANG MOTOR 110 cm3: EFFECT OF BIOETHANOL MIXTURE AND THERMAL CONDUCTIVITY OF THE ELECTRODE OF THE SPARK PLUG ON 110 cm3 MOTOR EXHAUST GAS EMISSIONS - Galang Manggala Yuda (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2022)
Bioethanol is analternative fuel to replace fossil oil. Bioethanol has several advantages in its use as fuel apart from its renewable nature, bioethanol is also believed to be able to reduce some motor vehicle emissions. Bioethanol hasan advantage over gasoline, namely a high octane number. However, bioethanol also has a weakness, namely having a low calorific value compared to fossil fuels. The purpose and objective of this study was to determine the effect of using a mixture of bioethanol and RON 92 fuel on exhaust emissions on matic injection motorcycleswith parameters measuring CO, HC, CO2, and O2. Tests on motor vehicles were carried out with mixed variations (0%, 5%, 10%, 15%, 20%) with variations of standard spark plugs and iridium spark plugs and the tests were carried out at 2000-6000 rpm with a multiple of 1000 rpm. The method used in this study is a quantitative method, namely the data obtained in the form of numbers. The data obtainedwill beprocessed and averaged to get a conclusion. In this data analysis, the researcher used two-way Anova. From the test, the highest HC results were found in the 20% mixture, namely 113.33 ppm at 2000 rpm and the lowest results were obtained, reaching35 ppm at 6000 rpm with a spark plug thermal conductivity of 147W/mK in a 5%mixture. The highest CO yield was obtained at 20% mixture at 2000 rpm with a spark plug electrode thermal conductivity of 90.7W/mK which reached 0.76% and the lowest yield reached 0.02% at 6000 rpm with a 0% mixture with a spark plug electrode thermal conductivity of 147W/mK. The highest CO2yield was at 15% mixture at 6000 rpm with a spark plug thermal conductivity of 90.7W/mK which reached 10.73% and the lowest yield reached 0.13% at 20% mixture at 2000 rpm. The highest O2yield at 15% mixture with a spark plug thermal conductivity of 90.7W/mK reached 0.28% at 6000 rpm and the lowest yield was obtained at 0% mixture at 2000 rpm